Literatur Review Big Data Analytics dalam Meningkatkan Keberlanjutan Triple Bottom Line: Studi Lintas Bidang Manajemen Risiko Bencana dan Supply Chain Manufaktur - Elpiah Risdayani; Bunga Ria Letisia Sirait; Juniansen Siregar (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study synthesizes findings from thirteen journals examining the role of big data analytics capabilities (BDAC) in risk management and manufacturing supply chain performance. The analysis shows that utilizing BDAC improves companies' ability to detect and mitigate risks in real time, including risks of supply disruptions, demand fluctuations, and compliance with environmental regulations. BDAC implementation also strengthens supply chain efficiency by optimizing procurement, distribution, and inventory control, while simultaneously encouraging innovation in environmentally friendly production processes. From an accounting perspective, the integration of big data with triple bottom line reporting emphasizes the role of accountants as providers of strategic information that supports sustainability-oriented decision-making. These findings emphasize that the success of risk management and management of modern manufacturing supply chains is highly dependent on the use of advanced analytics technologies as a basis for adaptive, efficient, and sustainable decision-making.